Sensory and Non-sensory Factors Behind the Liking and Choice of Healthy Food Products - Pohjanheimo, Terhi (fi=Turun yliopisto|en=University of Turku|, 2010)
A healthy and balanced diet can reduce health problems, such as overweight and metabolic syndrome. In general, people have a considerably good knowledge of what constitutes a healthy diet and how they could achieve it with their food choices. Besides, people argue that health is among their top five food choice motives. Nevertheless, the prevalence of overweight is increasing and other food choice motives, such as taste, seem to conflict with the health. Liking for food does not necessarily determine acceptance alone, thus several non-sensory factors, such as brand, country of origin and nutrition claim, can also influence. Moreover, consumers are individuals in how they prioritize sensory and nonsensory factors of foods, but e.g. increasing age, female gender and health concern have been connected to a more health-oriented dietary behaviour. To sum up, identifying different factors that can increase the liking and consumption of healthy food is essential in order to develop more attractive healthful food products. Adding vitamins, minerals, fibre or other ingredients to a food product can be used to enrich the nutritional quality of the products. However, this may be difficult in practice as regards the sensory quality and pleasantness of the foods. Generally, consumers are not willing to compromise on taste in food. On the other hand, consumers are very heterogeneous in their likings, and their personal values and attitudes may interact with preferences for specific sensory characteristics. The aims of this study were to investigate the effects of intrinsic product characteristics on sensory properties and hedonic responses; to determine the impact of few non-sensory factors; and to examine the interaction between sensory and non-sensory factors with consumers’ demographics, values and attitudes in liking of healthy model foods. The results showed that product composition influenced sensory quality and had an effect on hedonic responses. Adding flaxseed to bakery products showed a significant improvement in the nutritional quality without negative effects on sensory properties. On the other hand, the fortification of wellness beverages with vitamins and minerals may impart off-flavours. In general, sweetness of yoghurts, freshness of wellness beverages and low intensity of rye bread flavour appealed to consumers. Information about the domestic origin of yoghurts and claiming a specific function for wellness beverages enhanced liking. However, consumers who were more concerned about their health and considered natural content as an important food choice motive, rated sourer and less sweet yoghurts and wellness beverages as more pleasant. In addition, interest in health increased the consumption of rye breads and other whole grain breads among adolescents. The results showed that the optimal product quality in terms of intrinsic and extrinsic factors differs between individual consumers, and personal values and food choice motives can be connected to preferences for specific sensory characteristics of foods. This indicates that each food product needs to be considered in relation to its specific market niche, and to which segment of consumer will respond most positively to its characteristics.